FRUITS, SEEDS AND POLLEN MORPHOLOGY OF ALYSSUM L. (BRASSICACEAE) AND THEIR TAXONOMIC VALUE - Bülbül, Ali Savaş; Varlık, Kader; Armağan, Metin; Arslan, Adnan (My University, 2019)
In the current study, macro- and micromorphological characters of fruits, seeds, and pollen in Alyssum L. (14 to 19 species) were examined by stereo, light (LM) and scanning electron microscope (SEM) to evaluate the taxonomic significance of these characters. Detailed description of features of Turkish Alyssum species are provided with illustrations. Generally, the pollen grains are radially symmetrical and isopolar. The fruit surface is glabrous or stellate trichome. The seeds are ovate, spheroidal or oblong in shape among the studied species. The colors of the seed vary between light brown, dull yellow brownish, bright red brownish, dark brownish, dull light reddish, bright brownish, bright red brownish, dull brownish and dull yellowish. The surface of the seed is reticulate (normal reticulate, reticulate-foveate, reticulate-lineolate, reticulate-rugose), ruminate, rugose, lineolate, blister and colliculate in SEM. The pollen grains of the genus are subprolate or prolate. The pollen grains are tricolpate. Exine ornamentations are mainly reticulate. Ornamentations, pollen shape and size, aperture type, colpus length and width, fruit and seed shape, size and color, seed anti and periclinal walls have been observed as significant morphological characters.
Keywords: Alyssum L.; Fruit; Pollen; Seed; Light microscope; Turkey; Meyve; Polen; Tohum; Işık mikroskobu; Türkiye